First report of the genus Haritalodes Warren, 1890 from Micronesia (Lepidoptera, Crambidae, Spilomelinae), with description of a new species - Ko, Jae–Ho; Albert, Austin; Dasari, Ulziijargal Bayarsaikhan (Zootaxa, 2023)
N/A